Channel estimation for time varying channel based on decision directed technique in OFDM mobile systems - CHEN Hui; CHEN Xiao-guang (Tongxin xuebao)
A channel estimation method was proposed based on decision directed technique and pilot tracking for OFDM WLANS with mobile terminals. The result of training sequence based estimation was used as the initialization of decision directed technique. With the help of the decision symbols, the statistical characteristics of the transmitted data via the fading channel were applied for the channel estimation. Some reliable estimated results combined with pilot were used to track the change of the fading channel. The simulation results show that the proposed method has better performance than training sequence based or pilots based channel estimation method.